CRISPR/Cas9 Mutagenesis and Expression of Dominant Mutant Transgenes as Functional Genomic Approaches in Parasitic Nematodes - Lok, James B. (Frontiers in Genetics, 2019)
DNA transformation of parasitic nematodes enables novel approaches to validating predictions from genomic and transcriptomic studies of these important pathogens. Notably, proof of principle for CRISPR/Cas9 mutagenesis has been achieved in Strongyloides spp. allowing identification of molecules essential to the functions of sensory neurons that mediate behaviors comprising host finding, invasion and location of predilection sites by parasitic nematodes. Likewise, CRISPR/Cas9 knockout of the developmental regulatory transcription factor Ss-daf-16 has validated its function in regulating morphogenesis of infective third-stage larvae in Strongyloides stercoralis. While encouraging, these studies underscore challenges that remain in achieving straightforward validation of essential intervention targets in parasitic nematodes. Chief among these is the likelihood that knockout of multifunctional regulators like Ss-DAF-16 or its downstream mediator, the nuclear receptor Ss-DAF-12, will produce phenotypes so complex as to defy interpretation and will render affected worms incapable of infecting their hosts, thus preventing establishment of stable mutant lines. Approaches to overcoming these impediments could involve refinements to current CRISPR/Cas9 methods in Strongyloides including regulatable Cas9 expression from integrated transgenes and CRISPR/Cas9 editing to ablate specific functional motifs in regulatory molecules without complete knockout. Another approach would express transgenes encoding regulatory molecules of interest with mutations designed to similarly ablate or degrade specific functional motifs such as the ligand binding domain of Ss-DAF-12, while preserving core functions such as DNA binding. Such mutant transgenes would be expected to exert a dominant interfering effect on their endogenous counterparts. Published reports validate the utility of such dominant-negative approaches in Strongyloides.